Bioavailability of Orally Administered Des-Aspartate-Angiotensin I in Human Subjects - Lee, Kok-Onn (Drugs R D, 2017)
In an earlier single-dose escalation study to evaluate the safety and pharmacokinetics of orally administered des-aspartate-angiotensin I (DAA-I) in healthy subjects, the plasma level of DAA-I could not be determined because DAA-I is rapidly degraded in the circulation. The present study investigated the oral bioavailability of DAA-I by measuring the prostaglandin E(2) metabolite (PGEM) in the plasma samples of the same trial. PGEM is a stable derivative of PGE(2), which has been shown to be a biomarker of DAA-I. The data show that plasma from two of the three subjects who were orally administered the efficacious preclinical dose of 0.70 mg/kg DAA-I exhibited a significant PGEM peak at 5–6 h postdose. Plasma of subjects who were administered 0.08 and 1.5 mg/kg DAA-I, the subefficacious and two-times efficacious dose, respectively, did not exhibit a similar PGEM peak. This observation is concordant with the known in vivo actions of DAA-I, especially its hypoglycemic action where maximum efficacy occurred at a dose of 0.7 mg/kg, and decreased to nil at the two-times efficacious dose. The onset of the PGEM peak at 5–6 h postdose was closed to the 4-h onset of absorption of [C(14)]DAA-I seen in preclinical rat studies, albeit the absorption kinetics between rodents and humans are not identical. The occurrence of polymorphism of enzymes involved in the formation and degradation of PGE(2) is common, and this has been attributed to contributing to the variation in response, onset and peak PGEM observed among the three subjects who were administered the efficacious dose.